2022
DOI: 10.3390/en15165872
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance Analysis of Materials and Configurations for Cylindrical Sidewalls of Charcoal Kilns

Abstract: Most of the charcoal in the world comes from small and medium-sized producers, using rudimentary carbonization kilns that require significant time or energy during the heating and cooling stages of the process. Despite advances in improving the performance, the influence of materials used in the sidewalls of these kilns has been scarcely studied. Therefore, based on numerical simulations, the present study analyses the thermal performance of cylindrical sidewalls composed of combinations of metallic materials,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Meanwhile, heat absorption effectiveness reached 11.67% (for reactors without insulators) and 13.87% (for reactors with insulators), as shown in Figure 7. Valentim et al [10] confirmed the effectiveness of using insulators in carbonization reactors by demonstrating significant reductions in heating time. These reductions ranged from 66.0% to 99.7% when using different configurations of insulators in the reactors.…”
Section: Energy Use Effectivenessmentioning
confidence: 94%
See 2 more Smart Citations
“…Meanwhile, heat absorption effectiveness reached 11.67% (for reactors without insulators) and 13.87% (for reactors with insulators), as shown in Figure 7. Valentim et al [10] confirmed the effectiveness of using insulators in carbonization reactors by demonstrating significant reductions in heating time. These reductions ranged from 66.0% to 99.7% when using different configurations of insulators in the reactors.…”
Section: Energy Use Effectivenessmentioning
confidence: 94%
“…The presence of a moderate temperature difference ranging from 15 to 19℃ suggests that the clay insulators used to line the outer wall of the reactor may not be optimal because the water contained in the clay insulator evaporates due to heat transmission during the carbonization process from the walls to the insulator. This condition leads to the formation of cracks in the insulator, which facilitates the escape of heat into the ambient environment and consequently impacts heat loss [10].…”
Section: Figure 3 Temperature Distribution During the Carbonization P...mentioning
confidence: 99%
See 1 more Smart Citation
“…The natural cooling of the product requires a long time, drastically reducing productivity [1,22,24,25]. Given that the qualitative characteristics of the charcoal are not affected by cooling, this must take place as quickly as possible [25,92]. In the literature, several solutions are presented to accelerate the cooling process.…”
Section: Improvement In the Carbonization Processmentioning
confidence: 99%